Newsworthiness of Multiple Identity Organizations - Robert Heckert; Margot van der Goot (Social Sciences and Humanities Open, 2022)
Media reputation is an important asset of every organization but might even be more delicate for a multiple identity organization (MIO). MIOs usually have central, distinctive, and enduring characteristics belonging to two antithetical value systems, often the ideological and the utilitarian value system. This qualitative interview study explores journalists' understanding and coverage of MIOs and how both are impacted by journalistic role perceptions and by the nature and behavior of such organizations. The findings of this research provide insight into the journalistic production process and could be instructive for the media management of MIOs. The interviewees recognized the potentially problematic character of an MIO but were divided about the newsworthiness of organizational identity multiplicity. Besides a group of “explainer” journalists, who were neutral towards MIOs, there were “watchdog” journalists who were extra sharp-eyed when an MIO was involved. They observed a lack of transparency about the commercial goals and profits. Controversy in terms of internal and external tensions was found to be a particularly salient news value with respect to an MIO. During the COVID-19 pandemic the journalist's interest in the tension between the organization's identities seemed to disappear. The central conclusion is that organizational identity multiplicity may trigger the critical attention of journalists. MIOs should improve transparency, especially considering their commercial activities.